The Strength of a Story: Partnering With a Community Organization to Destigmatize Substance Use Disorder - Noah Sorkow; Cameron Lauf; Stephen H. Berns (MedEdPORTAL)
Introduction Stigmatizing attitudes held by health care professionals against individuals with substance use disorder (SUD) result in worse clinical outcomes. Story-listening has been shown to help mitigate bias for medical trainees. We created a narrative-based small-group facilitated discussion between medical students and an individual in recovery from SUD through a direct partnership with a community peer-recovery organization. Methods All session materials were formulated in direct partnership with the community organization. After completing prework, second-year medical students engaged in a 1.5-hour facilitated discussion with a community member in recovery and one attending physician preceptor. Student perceptions of the session and SUD were evaluated using open-ended and Likert-scale questions through an online survey. Community members engaged in their own postsession debrief. Results One hundred twenty-four second-year medical students, 16 attending physician preceptors, and 10 community members in recovery participated in the session. Students agreed or strongly agreed that they appreciated the session format (92%), that they learned something new about SUD (83%), and that the session was applicable to their future career (92%). Students appreciated the small-group format and hearing someone's lived experience/perspective. Community members expressed how the session helped humanize health care providers and had interest in participating in future sessions. Discussion Working in direct partnership with a local community organization to create an intimate narrative-based educational experience for medical students is feasible, appreciated by medical student participants, and mutually beneficial to community members and can facilitate positive changes in student knowledge and, potentially, bias regarding SUD.